Evaluation of Vaca and Caga Genotypes of Helicobacter Pylori in Iranian Patients with Peptic Ulcer Disease - Hossein Abadi, Ali Saber (2007)
Helicobacter pylori infection occurs all over the world, and more than half of the world population is infected by this microorganism. Research on the variety of H. pylori genes is valuable from two perspectives; first, for predicting the outcome of the infection and second, for better understanding of its distribution in the world and the evolutionary origins of this organism. It has been suggested that Helicobacter pylori strains containing cagA gene and the s1/m1 genotype of vacuolating cytotoxin gene A (vacA) may be associated with peptic ulcer diseases. Some studies have also shown that allele s1 of the vacA gene is associated with gastroduodenal diseases In order to investigate the cagA and vacA genes, biopsies of the antrum and corpus of the stomachs of patients were obtained. To detect H. pylori infection, the phosphoglucosamine mutase gene (glmM) was amplified through the PCR method and observed on 2% (w/v) agarose gel electrophoresis. All the H. pylori-positive samples were subjected to further PCR amplification to determine different alleles of the vacA gene. The PCR products were separated on 2% (w/v) agarose gels electrophoresis. 37, 15 and 32 out of 84 specimens were duodenal ulcer (DU), gastric ulcer (GU) and gastritis (GT), respectively. Seventy-seven (91.7%, χ2= 58.333, p < 0.05) out of 84 samples were H. pylori-positive. cagA gene was detected in 80% (χ2= 12.6, p < 0.001), 76.9% (χ2= 3.769, p > 0.05), and 48.3% (χ2= 0.034 p > 0.05) from DU, GU and GT samples, respectively. It was found that 66% (23/35) of DU samples, 62% (8/13) of GU samples and none of 29 GT samples were s1/m1. 17% (6/35) of DU samples, 15% (2/13) of GU samples and 52% (16/29) of GT samples were s1/m2. 17% (6/35) of DU samples, 23% (3/13) of GU samples and 48% (13/29) of GT samples were s2/m2. This study demonstrates that the presence of the m2 allele of vacA is strongly associated with gastritis and the presence of allele s1 is associated with peptic ulcers. Helicobacter pylori strains with vacA-s1/m2-cagA+ genotype are associated with peptic ulceration diseases.